Indians and indigenistic art i0n latin-america in the early 20th century (2005)
The subjects of Indians and the indigenous, two similarbut different approaches, were dealt-with during thesecond half of the 19th century by some Mexican andPeruvian painters, sculptors, and architects. Theyfounded an attitude which prolonged itself as an artisticrenewal into the 20th century thanks to the work ofmany artists. The first was José Guadalupe Posada, whotreated a variety of subjects from the point of view ofthe indigenous and was followed by a member of thenext generation: José Sabogal, a collaborator in JoséCarlos Mariátegui’s Amauta and the earliest Latin-American indigenistic painter, whose preferred subjectwere Indians themselves.